Draft Annual Plan 2011-2012 Volume-II A (Statistical Tables) - Planning Commission (Planning Commission, 2011)
Proposed Outlays - Major Heads / Minor Heads of Development Proposed Outlay on Continuing and New Schemes Proposed Outlay on Continuing and New Schemes.
(Statistical Tables)